Random Illumination Microscopy: faster, thicker, and aberration-insensitive - Boya Jin; Peng Xi (Light: Science & Applications)
Abstract The Extended Depth of Field (EDF) approach has been combined with Random Illumination Microscopy (RIM) to realize aberration-insensitive, fast super-resolution imaging with extended depth, which is a promising tool for dynamic imaging in larger and thicker live cells and tissues.